The Delft Systems Approach - Veeke, Hans P. M. (Springer, 2017)
The pace of development in knowledge and know-how in the fields of organisational sciences, logistics and information technology is rapid. However, the gap between the researcher in these areas and the practicing manager is growing. The Delft Systems Approach sets out to close the gap between theory and practice, and to achieve the following goals: